Inovasi Metode Konstruksi Prefabrikasi untuk Efisiensi Biaya dan Waktu pada Proyek Gedung Tinggi Perum Perumnas - Sari, Yusra Aulia; Dinata, Yanweri (MEDIA KOMUNIKASI TEKNIK SIPIL, 2022)
Prefabrication has been widely used in construction projects. Prefabrication improves construction speed, architectural quality, material efficiency, and worker safety while limiting construction's environmental impact than conventional construction practices built on site. This research explains the advantages of prefabricated construction methods and offers an alternative method for innovation for the High Rise Building Project of Perum Perumnas. The prefabrication method is an alternative solution based on the SWOT analysis, and software for modeling and structural design is STAAD.Pro V8.I by Bentley System, inc. The research results have shown that prefabrication methods in the High Rise Building Project of Perum Perumnas can save 7% (deviation = 868.47 million) more than the current construction method (conventional). In terms of time, the prefabrication method is faster than traditional methods, with a time difference of 371 days. The estimated time required to complete upper structure work using conventional methods is 557 days. In comparison, the time needed to complete upper structure work with prefabricated methods is only 186 days, assuming the working time is eight hours per day. And the risk analysis is generally mentioned. Therefore, based on the calculation results, it can be concluded that the prefabrication method can increase the number and quality of development production in the High Rise Building Project of Perum Perumnas.